(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Estimating the post-mortem time interval (PMI) is a crucial component of the forensic investigation and is extremely difficult for medico-legal experts to do. After death, the succession of microbes in various parts of the human body has enormous potential for predicting PMI. The human body is home to trillions of commensal microorganisms. These microbes behave in a different way when biological processes stop, which coincides with the death of an individual and the invasion of deteriorating microbes from the environment. Due to cell autolysis, which draws a variety of invasive macro- and microorganisms, human cadavers become a rich source of nutrients. The succession of microorganisms differs significantly at various stages of degradation, which can be investigated for precise PMI estimation. Necrobiome analysis has drawn a lot of attention in PMI estimation due to the development of microbial genomics technology and decrease in the price of DNA sequencing. The review article provides a summary of the various microorganism sources, their successional pattern, and analytical methods that can be used in the field of microbial forensics.